Effects of the Novel Non-steroidal Anti-inflammatory Compound [N-(2-Thiol-ethyl)-2-{2-[N'-(2,6-dichlorophenyl) amino]phenyl} acetamide on Cytokines and Apoptosis in Ischaemic Rat Brain - Peroulis, Nikos; Kourounakis, Angeliki P.; Yiangou, Minas; Paramythiotis, Daniel; Kotzampassi, Katerina; Hadjipetrou, Lygeri (Arzneimittelforschung, 2006)
Ischaemia-reperfusion injury is associated with an inflammatory response as well as apoptosis in the affected area. Inflammatory responses are characterized, among others, by an increased production of several cytokines, while caspases are implicated in the control of apoptosis. The aim of the present work was to determine changes in the levels of inflammatory and apoptotic indices in the rat brain after cerebral ischaemia-reperfusion and to evaluate the effect of the non-steroidal anti-inflammatory compound N-(2-thiolethyl)-2-{2-[N'-[2,6-dichlorophenyl)amino]phenyl} acetamide on these indices. A cerebral ischaemia-reperfusion rodent model was used to investigate, via immunohistoch-emical and colorimetric techniques, the presence in the brain and spleen of inflammatory enzymes cycloxygenases COX-1 and COX-2, cytokines interleukin (IL)-1ß, IL-4, IL-6, IL-10, IL-18, tumor necrosis factor alpha (TNF-a) and interferon gamma (IFN-γ) as well as the activated form of caspase-3, in treated and untreated animals. Cerebral ischaemia-reperfusion caused elevated levels in the rat brain of all enzymes and cytokines included in this study, at 1, 3 and 5 dayspost ischaemia. Treatment with the antiinflammatory derivative reduced the elevation, caused by ischaemia, of IFN-y, TNF-a, IL-1ß IL-6, IL-18 and caspase-3 levels at 3 days post ischaemia, while it increased the levels of IL-10. It was shown that the increase in concentrations of a wide range of cytokines involved in the inflammatory reaction causing brain damage after ischaemia-reperfusion can be partially reversed by the anti-inflammatory derivative used in this study.
Keywords: Anti-inflammatories, non-steroidal; Apoptosis; Cerebral ischaemia; Cytokines; N-(2-Thiolethyl)-2-{2-[N'-(2,6- dichlorophenyl) amino] phenyl}acetamide; effects on cytokines and apoptosis, rat